Artificial intelligence contribution to recruitment and selection - Lopes da Costa, R.; Costa, B.; Martinho, F.; Pereira, L.; Gonçalves, R.; Dias, Á. (International Journal of Management Practice, 2023)
The current organisations are increasingly living in a technological and competitive context, and there is a need to implement new techniques, especially in the area of human resource management. Based on the use of a methodology focused on semi-structured interviews, applied to 19 experts in the area of intelligent systems and human resource management, it was possible to conclude that human resource management is in a phase of growth and learning, and that there is still a great reluctance towards artificial intelligence. However, many experts argue that the introduction of artificial intelligence is a natural process that will allow jobs to be always renewable.